PMP : - Heldman, Kim (Wiley Pub., 2007)
Full coverage of all exam objectives in a systematic approach, so you can be confident you're getting the instruction you need for the exam Bonus workbook section with over 200 pages of exercises to help you master essential charting and diagramming skills Practical hands-on exercises to reinforce critical skills Real-world scenarios that put what you've learned in the context of actual job roles Challenging review questions in each chapter to prepare you for exam day Exam Essentials, a key feature in each chapter that identifies critical areas you must become proficient in before taking the exam A handy tear card that maps every official exam objective to the corresponding chapter in the book, so you can track your exam prep objective by objective.